2005
DOI: 10.1002/cncr.20917
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of the ubiquitin ligase subunits Skp2 and Cks1 in colorectal carcinoma

Abstract: BACKGROUNDLoss of the cell‐cycle inhibitory protein p27Kip1 is associated with poor prognosis in colorectal carcinoma. The decrease in p27Kip1 levels is the result of increased proteasome‐dependent degradation, mediated and rate‐limited by its specific ubiquitin ligase subunits S‐phase kinase protein (Skp) 2 and cyclin‐dependent kinase subunit (Cks) 1. Recently, Skp2 and Cks1 expression were found to be increased in some colorectal carcinomas, but their potential role as prognostic markers for survival is unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
115
1
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(129 citation statements)
references
References 22 publications
12
115
1
1
Order By: Relevance
“…97 Skp2/Cks1 are inversely related in Cks1 and Skp2 null animals 30,84 and many human cancers. 46,[85][86][87][88] Moreover, B-RAF and cyclin D1 upregulate Cks1 and Skp2, and Myc induces Cks1 for p27 degradation in certain human cancers. 89,90 Our data demonstrate that 4 hr after treatment with TGFβ, Cks1 mRNA is slightly upregulated and then decreased to basal levels by 24 hr.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…97 Skp2/Cks1 are inversely related in Cks1 and Skp2 null animals 30,84 and many human cancers. 46,[85][86][87][88] Moreover, B-RAF and cyclin D1 upregulate Cks1 and Skp2, and Myc induces Cks1 for p27 degradation in certain human cancers. 89,90 Our data demonstrate that 4 hr after treatment with TGFβ, Cks1 mRNA is slightly upregulated and then decreased to basal levels by 24 hr.…”
Section: © 2 0 0 9 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…Increases in Cks1 expression have been shown in a number of human malignancies (1)(2)(3)(4). Increase in Cks1 mRNA has also been shown in PyMT-initiated mammary tumors (17), and in urethane and ENU-initiated lung tumors in rasH2 mice (32).…”
Section: Discussionmentioning
confidence: 95%
“…Cyclin kinase subunit 1 (Cks1) is a small protein whose expression is strongly associated with aggressive breast tumors, prostate carcinomas, non-small cell lung cancers, and several other malignancies (1)(2)(3)(4). Cks1 was shown to associate with Skp2, a subunit of the SCF Skp2 ubiquitin ligase which mediates the ubiquitin-dependent proteolysis of the cdk inhibitor p27…”
Section: Introductionmentioning
confidence: 99%
“…The discovery of useful molecular markers involved in crucial steps of carcinogenesis provides information on MST behavior, yet applying their use to the understanding of histogenesis is less common. Human cancer, manifested as uncontrolled cellular proliferation, is commonly caused by changes in the expression or activity of proteins involved in regulating the normal cell cycle [13]. p27, a member of the cip/kip family of cyclin-dependent kinase inhibitors, is expressed at high levels in G o cells and promotes cell arrest and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…p27, a member of the cip/kip family of cyclin-dependent kinase inhibitors, is expressed at high levels in G o cells and promotes cell arrest and apoptosis. The protein that specifically binds and targets p27 for degradation is S-phase kinase associated protein-2 (skp-2), and may be the main rate-limiting regulator for p27 degradation [13]. Previous studies on a variety of human cancers showed that an altered p27/skp-2 ratio was associated with poorer differentiation, aggressive biological behavior and worse clinical outcome [14][15][16].…”
Section: Introductionmentioning
confidence: 99%